2020
DOI: 10.1016/j.ejps.2019.105170
|View full text |Cite
|
Sign up to set email alerts
|

Establishing virtual bioequivalence and clinically relevant specifications using in vitro biorelevant dissolution testing and physiologically-based population pharmacokinetic modeling. case example: Naproxen

Abstract: Background: Physiologically-based population pharmacokinetic modeling (popPBPK) coupled with in vitro biopharmaceutics tools such as biorelevant dissolution testing can serve as a powerful tool to establish virtual bioequivalence and set clinically relevant specifications. One of several applications of popPBPK modeling is in the emerging field of virtual bioequivalence (VBE), where it can be used to streamline drug development by implementing model-informed formulation design and to inform regulatory decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 74 publications
(99 reference statements)
1
41
0
Order By: Relevance
“…The pH in the acceptor compartment was frequently monitored and, when necessary, adjusted with defined volumes of 1 M sodium hydroxide solution in order to maintain a stable pH. Sampling at specified time points (1,3,5,7,9,11,15,20,25,30,35,45,60,70,80, 90, 120 min) from the acceptor compartment and quantification of the API content was performed analogous to the procedure described in the previous section.…”
Section: Transfer Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH in the acceptor compartment was frequently monitored and, when necessary, adjusted with defined volumes of 1 M sodium hydroxide solution in order to maintain a stable pH. Sampling at specified time points (1,3,5,7,9,11,15,20,25,30,35,45,60,70,80, 90, 120 min) from the acceptor compartment and quantification of the API content was performed analogous to the procedure described in the previous section.…”
Section: Transfer Testmentioning
confidence: 99%
“…In contrast to amoxicillin, doxycycline has a long pharmacokinetic elimination half-life (12e25 h 27 ), high permeability (P app [Â10 À6 cm/s] ¼ 17.5 ± 0.3 in a Caco-2 monolayer system 28 ) and a late t max of 1.5e3.5 h. 27 For such APIs, it was suggested that wider dissolution criteria could be acceptable for a BCS-based biowaiver, as minor differences in dissolution are unlikely to have an influence on pharmacokinetic outcome parameters for the assessment of bioequivalence. 26,29,30 Commercially available formulations of doxycycline contain the API in the form of either the monohydrate or the hyclate salt. The bioavailability of a 200 mg dose is high for both forms (mean fraction absorbed of 95% 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…In another words, the average value of relative bioavailability can be protected through the cross-over design, however, overlooking the intraindividual variability may fail to capture the true confidence interval around the mean. Thus, to prevent any crossover virtual bioequivalence trials (VBE) becoming associated with false positive or false negative results (compared to any real large scale BE results), it is crucial to inform the models with correct estimates of within subject variability (11). Furthermore, this iterative modeling workflow can accommodate the IVIVC for various in vivo conditions (patients vs healthy subjects, stratified populations, etc.)…”
Section: Current Scientific Considerations For Supporting Bcs III Drug Waiver and Modeling Bcs Iii Drug Absorptionmentioning
confidence: 99%
“…The second option is to include the intraindividual variability in the system parameters and to propagate it through simulations (Wedagedera et al., 2017). In one of the recent examples of VBE with naproxen where intraindividual variability was propagated through simulations, its value was arbitrarily chosen to be 30% and it was added to selected GI parameters, for example, mean gastric emptying time, gastric and intestinal pH and bile salts concentration (Loisios‐Konstantinidis et al., 2020). In that way, predicted variability and derived 90% confidence intervals may get inflated.…”
Section: Current Scientific Considerations For Supporting Bcs III Drug Waiver and Modeling Bcs Iii Drug Absorptionmentioning
confidence: 99%
“…12-15 PBPK models with enhanced population simulation capabilities can be used to support virtual BE (VBE) assessments. [16][17][18][19][20] Previously, mechanistic dermal PBPK models have been used to describe the permeation through the skin for environmental and other chemicals and perform risk-based assessments. 21,22 For locally acting drug products, including those applied on the skin, although administered at or close to the site of action, quantification of active ingredient amounts at the site of action for BE assessments is often not feasible.…”
Section: Introductionmentioning
confidence: 99%